An Efficient Approach for the Design and Synthesis of Antimicrobial Peptide-Peptide Nucleic Acid Conjugates - Patil, Nitin A.; Thombare, Varsha J.; Li, Rong; He, Xiaoji; Lu, Jing; Yu, Heidi H.; Wickremasinghe, Hasini; Pamulapati, Kavya; Azad, Mohammad A. K.; Velkov, Tony; Roberts, Kade D.; Li, Jian (Frontiers in Chemistry, 2022)
Peptide-Peptide Nucleic Acid (PNA) conjugates targeting essential bacterial genes have shown significant potential in developing novel antisense antimicrobials. The majority of efforts in this area are focused on identifying different PNA targets and the selection of peptides to deliver the peptide-PNA conjugates to Gram-negative bacteria. Notably, the selection of a linkage strategy to form peptide-PNA conjugate plays an important role in the effective delivery of PNAs. Recently, a unique Cysteine- 2-Cyanoisonicotinamide (Cys-CINA) click chemistry has been employed for the synthesis of cyclic peptides. Considering the high selectivity of this chemistry, we investigated the efficiency of Cys-CINA conjugation to synthesize novel antimicrobial peptide-PNA conjugates. The PNA targeting acyl carrier protein gene (acpP), when conjugated to the membrane-active antimicrobial peptides (polymyxin), showed improvement in antimicrobial activity against multidrug-resistant Gram-negative Acinetobacter baumannii. Thus, indicating that the Cys-CINA conjugation is an effective strategy to link the antisense oligonucleotides with antimicrobial peptides. Therefore, the Cys-CINA conjugation opens an exciting prospect for antimicrobial drug development.